Catalyst for sulfuric acid production
By doping samarium elements into the vanadium catalyst and using modified diatomaceous earth and mesoporous material support, the problem of poor low-temperature activity of vanadium catalyst is solved, and the high activity and stability of the catalyst in a wide temperature range is achieved.
Patent Information
- Application Number
- CN202510724856.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-03
- Publication Date
- 2025-07-04
- Estimated Expiration
- 2045-06-03
AI Technical Summary
The existing vanadium catalysts have poor catalytic activity at low temperatures, and the blockage of the pores leads to a reduced catalytic activity, making it impossible to effectively adsorb and oxidize sulfur dioxide.
The vanadium catalyst is doped with samarium elements, modified diatomaceous earth and mesoporous materials are used as support, and pores are expanded by sonication of dilute sulfuric acid solution, and the catalyst is prepared by impregnation method to avoid uneven dispersion of active components caused by mixing and grinding.
The low-temperature activity and catalytic activity of vanadium catalyst are improved, and it has the advantages of anti-powder, high strength, low ignition temperature, and good activity stability. The catalytic activity is good within a wide temperature range.
Smart Images

Figure CN120243004A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of chemical engineering, and particularly relates to a catalyst for sulfuric acid production. Background Art
[0002] Vanadium catalyst is an essential chemical material in the contact process for sulfuric acid production. With the acceleration of China's industrialization process, the production scale and capacity of sulfuric acid have increased rapidly. At the same time, with the increasingly high environmental protection requirements, reducing the emission of SO2 in the tail gas of sulfuric acid production has become the focus of attention and the key point of research, which also increasingly raises the performance requirements for vanadium catalysts used in sulfuric acid production.
[0003] The existing method for preparing vanadium catalyst is to dissolve potassium hydroxide with steam in a reaction kettle, add vanadium pentoxide to prepare vanadium water, then add dilute sulfuric acid for neutralization to prepare the active material for the catalyst, and then mix, disperse, extrude into strips, dry and calcine with diatomite, alkali metal sulfate, sulfur powder, etc. to finally obtain the vanadium catalyst product. However, the vanadium catalyst only has high activity above 430°C. This is because at low temperatures, the active components in the vanadium catalyst react with SO2, and at too low temperatures, it is not conducive to the decomposition of vanadyl sulfate, which is produced by side reactions, into pentavalent vanadium compounds, sulfur dioxide and sulfur trioxide. This is also the reason why traditional vanadium catalysts have a high ignition temperature and poor low-temperature activity. In addition, impurities such as Al, Fe, and Ca in diatomite are distributed on the outer surface and inside the pores of diatomite, blocking some pores. This will hinder the adsorption and diffusion of active components on the surface and in the pores of diatomite during the catalyst manufacturing process. The blocked pores in the catalyst reduce the utilization rate of the inner surface. When participating in the reaction, SO2 and O2 cannot diffuse into the channels for deep oxidation reaction, and at the same time, the formed SO3 cannot be removed in time. The blocked gas inlet and outlet directly lead to a decrease in catalytic activity.
[0004] The Chinese patent application document with the publication number CN111036242A discloses a vanadium-based catalyst for wet conversion to sulfuric acid, which includes vanadium oxide, potassium sulfate, sodium sulfate, and a promoter supported on a carrier. The promoter is selected from at least one of phosphorus oxide and cesium sulfate, and the carrier includes diatomite. By adding a promoter to diatomite for hydrothermal treatment, the amorphous SiO2 in diatomite undergoes a crystal form transformation to become crystalline SiO2 with good stability, obtaining a synthetic carrier with hydrothermal stability. However, at low temperatures, the active components of this vanadium-based catalyst react with SO2, which is not conducive to the decomposition of vanadyl sulfate produced by side reactions, so the low-temperature activity is poor. The Chinese patent application document with the publication number CN110624570A discloses a preparation method for a low-temperature wet conversion to sulfuric acid vanadium catalyst, specifically: adding silica sol when preparing the catalyst active phase, and then mixing it with alkali metal sulfates, a promoter, refined diatomite, etc. in a mill, mixing evenly and compacting by rolling, and finally making the catalyst finished product through processes such as extrusion, drying, and roasting. The catalyst prepared by this method has characteristics such as anti-pulverization, high strength, and stable activity. However, the structure of diatomite will be damaged during the rolling process, and the impurity components in diatomite will block the pore structure of diatomite, resulting in a sharp decrease in the adsorption amount of the active components by diatomite, so the catalytic activity of the catalyst is low. Summary of the Invention
[0005] In order to solve the technical problems such as poor low-temperature activity and low catalytic activity of the catalyst existing in the above-mentioned prior art, the object of the present invention is to provide a catalyst for sulfuric acid production.
[0006] In order to achieve the above object, the technical solution of the present invention is as follows: A catalyst for sulfuric acid production is prepared by the following steps: S1: Dissolve potassium hydroxide in deionized water, stir evenly, heat, add vanadium pentoxide and sodium sulfate, and stir evenly to obtain solution I; S2: Add concentrated sulfuric acid to solution I obtained in step S1 under stirring, adjust the pH value of the solution to 2-4, and add Sm(NO3)3·6H2O to obtain solution II; S3: Add modified diatomite and mesoporous material to solution II prepared in step S2, stir evenly, then perform ultrasonic treatment, form, dry, and calcine to obtain a catalyst for sulfuric acid production; the mesoporous material is composed of mesoporous silica and mesoporous carbon according to a mass ratio of 9-12:4-7.
[0007] In the catalytic oxidation reaction of sulfur dioxide by vanadium catalyst, the main role is to adsorb oxygen and sulfur dioxide, play a bridging role, and enable sulfur dioxide to react with oxygen. The key component is V 5+And surface chemically adsorbed oxygen. In the present invention, samarium element is doped into the vanadium catalyst. The samarium element is a variable valence element, and its oxide has good oxygen storage capacity in rich oxygen and can release oxygen in poor oxygen. Therefore, doping with samarium element can effectively improve the oxygen adsorption capacity of the vanadium catalyst, which is beneficial to improving the catalytic activity of the vanadium catalyst. In addition, the samarium element has excellent activity at low temperatures, and the doping of the samarium element can also solve the technical problem of low activity of the vanadium catalyst at low temperatures. In the present invention, modified diatomite and mesoporous material are jointly used as the carrier, which can improve the dispersion degree of the active components on the catalyst. The vanadium catalyst is prepared by the impregnation method, effectively avoiding the problem of uneven dispersion of the active components caused by the mixing and grinding method, and then improving the catalytic activity of the catalyst.
[0008] Further, the preparation method of the modified diatomite in step S3 is as follows: Add dry diatomite into a dilute sulfuric acid solution, carry out ultrasonic treatment under stirring, filter by suction, dry, and grind to obtain the modified diatomite.
[0009] In the present invention, the diatomite is modified with a dilute sulfuric acid solution under ultrasonic conditions. It is found that under ultrasonic conditions, the dilute sulfuric acid solution can react with the iron impurities in the diatomite, playing a role in expanding the pores, thereby increasing the specific surface area of the diatomite. The adsorption capacity of the vanadium catalyst prepared with the modified diatomite for the active components increases, and the catalytic activity of the vanadium catalyst is improved.
[0010] Furthermore, in the preparation method of the modified diatomite, the mass ratio of the diatomite to the dilute sulfuric acid solution is 1:4 - 6, the concentration of the dilute sulfuric acid solution is 3 - 4 mol / L; the frequency of the ultrasonic treatment is 500 - 550 kHz, and the ultrasonic treatment time is 30 - 40 min.
[0011] Further, the preparation method of the mesoporous silica in step S3 is as follows: Dissolve tetramethylammonium hydroxide in pentanol, add ammonia water and ether, stir evenly, dropwise add tetraethyl orthosilicate, stir and react, filter by suction, dry, and calcine to obtain mesoporous silica.
[0012] In the present invention, tetramethylammonium hydroxide is used as the template and tetraethyl orthosilicate is used as the silicon source to prepare mesoporous silica with a connected pore structure by the sol - gel method. The active components in the vanadium catalyst can diffuse into the mesoporous silica through the connected pore channels, increasing the active sites of the vanadium catalyst, and then improving the catalytic activity of the vanadium catalyst.
[0013] Furthermore, the weight parts of each component in the preparation method of the mesoporous silica are: 5 - 8 parts of tetramethylammonium hydroxide, 30 - 40 parts of pentanol, 8 - 10 parts of ammonia water, 15 - 20 parts of ether, and 25 - 30 parts of tetraethyl orthosilicate.
[0014] Furthermore, in the preparation method of mesoporous silica, the stirring reaction time is 4.2 - 4.5 h, the calcination temperature is 500 - 550 °C, and the calcination time is 3.5 - 4 h.
[0015] Further, the preparation method of mesoporous carbon in step S3 is as follows: The dried wheat bran is calcined under a nitrogen atmosphere, cooled, mixed evenly with potassium hydroxide, and then continuously calcined under a nitrogen atmosphere. After cooling, it is ground, washed with hydrochloric acid aqueous solution until neutral, and dried to obtain mesoporous carbon.
[0016] In the present invention, the carbonized biomass material (wheat bran) is mixed with the activator potassium hydroxide and then prepared into a porous carbon material with different pore structures and morphologies through calcination. It jointly forms the carrier of the vanadium catalyst with modified diatomite and mesoporous silica, effectively increasing the active sites of the vanadium catalyst, and further enhancing the activation performance of the catalyst.
[0017] Furthermore, in the preparation method of mesoporous carbon, the calcination temperature is 750 - 800 °C, and the calcination time is 0.8 - 1.2 h; the temperature of the continuous calcination is 800 - 850 °C, and the continuous calcination time is 4.2 - 4.5 h; the mass ratio of wheat bran to potassium hydroxide is 1:2 - 3; the concentration of the hydrochloric acid aqueous solution is 0.5 - 0.8 mol / L.
[0018] Further, the heating temperature in step S1 is 70 - 75 °C; the ultrasonic frequency in step S3 is 200 - 250 kHz, the ultrasonic time is 10 - 12 h, the drying temperature is 90 - 100 °C, the drying time is 20 - 24 h, the calcination temperature is 550 - 600 °C, the heating rate during calcination is 5 - 10 °C / min, and the calcination time is 5.5 - 6 h.
[0019] Further, the weight parts of each component are: 15 - 20 parts of potassium hydroxide, 35 - 40 parts of deionized water, 5 - 10 parts of vanadium pentoxide, 2 - 3 parts of sodium sulfate, 1 - 2 parts of Sm(NO3)3·6H2O, 25 - 30 parts of modified diatomite, and 10 - 15 parts of mesoporous material.
[0020] Compared with the prior art, the catalyst for sulfuric acid production provided by the present invention has the following technical advantages: (1) The present invention uses samarium element for doping, effectively improving the catalytic activity and low-temperature activity of the vanadium catalyst, so that it has good catalytic activity in a relatively wide temperature range; (2) The present invention selects modified diatomite and mesoporous material to jointly form the carrier, effectively increasing the dispersion degree of the active components on the catalyst, which is beneficial to improving the catalytic activity of the catalyst; (3) In the present invention, diatomite is modified with dilute sulfuric acid solution under ultrasonic conditions to increase the specific surface area of diatomite, thereby improving the catalytic activity of the vanadium catalyst. (4) The catalyst for sulfuric acid production provided by the present invention has the advantages of anti-pulverization, high strength, low ignition temperature, good activity stability, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a self-made activity evaluation device; Figure 2 is a scanning electron microscope image of the catalyst prepared in Example 3; Figure 3 is an XRD pattern of the catalyst prepared in Example 3; Figure 4 is a pore size distribution diagram of the catalyst prepared in Example 3; Figure 5 is an adsorption-desorption curve diagram of the catalyst prepared in Example 3.
[0022] Figure 1 In 1-1, 1-2, 1-3 are buffer bottles, 2-1, 2-2 are drying bottles, 3-1, 3-2 are flow controllers (display instruments), 4 is a reactor, 5 is a collection bottle, 6-1, 6-2 are SO2 absorption tubes, 7-1, 7-2 are gas measuring cylinders (tubes), 8-1 is a leveling bottle, and 9 is an absorption bottle. DETAILED DESCRIPTION OF THE INVENTION
[0023] The following will be further described in conjunction with specific embodiments, but the present invention is not limited to the following embodiments. Those skilled in the art can make various modifications according to the basic idea of the present invention, but as long as they do not depart from the basic idea of the present invention, they are within the scope of the present invention.
[0024] Example 1 A catalyst for sulfuric acid production is prepared by the following steps: S1: Dissolve 15 g of potassium hydroxide in 40 g of deionized water, stir evenly, heat to 70 °C, add 5 g of vanadium pentoxide and 2 g of sodium sulfate, and stir evenly to obtain Solution I; S2: Add concentrated sulfuric acid to Solution I obtained in step S1 under stirring, adjust the pH value of the solution to 2, and add 1 g of Sm(NO3)3·6H2O to obtain Solution II; S3: Add 25 g of modified diatomite and 10 g of mesoporous material to Solution II prepared in step S2, stir evenly, ultrasonic for 10 h at 200 kHz, form, dry at 90 °C for 20 h, and calcine at 550 °C for 5.5 h (heating rate is 5 °C / min) to obtain a catalyst for sulfuric acid production; the mesoporous material is composed of mesoporous silica and mesoporous carbon in a mass ratio of 9:4.
[0025] The preparation method of the modified diatomite described in step S3 is as follows: Add dry diatomite into a dilute sulfuric acid solution with a concentration of 3 mol / L (the mass ratio of diatomite to the dilute sulfuric acid solution is 1:4), perform ultrasonic treatment under stirring (ultrasonic treatment at 500 kHz for 30 min), filter by suction, dry, and grind to obtain the modified diatomite.
[0026] The preparation method of the mesoporous silica described in step S3 is as follows: Dissolve 5 g of tetramethylammonium hydroxide in 30 g of pentanol, add 8 g of ammonia water and 15 g of ether, stir evenly, dropwise add 25 g of tetraethyl orthosilicate, stir and react for 4.2 h, filter by suction, dry, and calcine at 500 °C for 3.5 h to obtain the mesoporous silica.
[0027] The preparation method of the mesoporous carbon described in step S3 is as follows: Calcinate the dried wheat bran in a nitrogen atmosphere at 750 °C for 0.8 h, cool and mix evenly with potassium hydroxide (the mass ratio of wheat bran to potassium hydroxide is 1:2), continue to calcine in a nitrogen atmosphere at 800 °C for 4.2 h, cool and grind, wash with a hydrochloric acid aqueous solution with a concentration of 0.5 mol / L until neutral, and dry to obtain the mesoporous carbon.
[0028] Example 2 A catalyst for sulfuric acid production is prepared by the following steps: S1: Dissolve 20 g of potassium hydroxide in 35 g of deionized water, stir evenly, heat to 75 °C, add 10 g of vanadium pentoxide and 3 g of sodium sulfate, and stir evenly to obtain solution I; S2: Add concentrated sulfuric acid to solution I obtained in step S1 under stirring, adjust the pH value of the solution to 4, and add 2 g of Sm(NO3)3·6H2O to obtain solution II; S3: Add 30 g of modified diatomite and 15 g of mesoporous material to solution II prepared in step S2, stir evenly, perform ultrasonic treatment at 250 kHz for 12 h, form, dry at 100 °C for 24 h, and calcine at 600 °C for 6 h (heating rate is 10 °C / min) to obtain the catalyst for sulfuric acid production; the mesoporous material is composed of mesoporous silica and mesoporous carbon according to a mass ratio of 12:7.
[0029] The preparation method of the modified diatomite described in step S3 is as follows: Add dry diatomite into a dilute sulfuric acid solution with a concentration of 4 mol / L (the mass ratio of diatomite to the dilute sulfuric acid solution is 1:6), perform ultrasonic treatment under stirring (ultrasonic treatment at 550 kHz for 40 min), filter by suction, dry, and grind to obtain the modified diatomite.
[0030] The preparation method of the mesoporous silica described in step S3 is as follows: Dissolve 8 g of tetramethylammonium hydroxide in 40 g of pentanol, add 10 g of ammonia water and 20 g of ether, stir evenly, dropwise add 30 g of tetramethyl orthosilicate, stir and react for 4.5 h, filter by suction, dry, and calcine at 550 °C for 4 h to obtain mesoporous silica.
[0031] The preparation method of the mesoporous carbon described in step S3 is as follows: Calcinate the dried wheat bran in a nitrogen atmosphere at 800 °C for 1.2 h, cool it and mix it evenly with potassium hydroxide (the mass ratio of wheat bran to potassium hydroxide is 1:3), continue to calcine in a nitrogen atmosphere at 850 °C for 4.5 h, cool it and grind it, wash it with a hydrochloric acid aqueous solution with a concentration of 0.8 mol / L until neutral, and dry it to obtain mesoporous carbon.
[0032] Example 3 A catalyst for sulfuric acid production is prepared by the following steps: S1: Dissolve 18 g of potassium hydroxide in 37 g of deionized water, stir evenly, heat to 73 °C, add 8 g of vanadium pentoxide and 2.3 g of sodium sulfate, and stir evenly to obtain solution I; S2: Add concentrated sulfuric acid to solution I obtained in step S1 under stirring, adjust the pH value of the solution to 3, and add 1.5 g of Sm(NO3)3·6H2O to obtain solution II; S3: Add 28 g of modified diatomaceous earth and 13 g of mesoporous material to solution II prepared in step S2, stir evenly, ultrasonic wave at 230 kHz for 11 h, form, dry at 98 °C for 22 h, and calcine at 580 °C for 5.7 h (heating rate is 8 °C / min) to obtain a catalyst for sulfuric acid production; the mesoporous material is composed of mesoporous silica and mesoporous carbon according to a mass ratio of 11:6.
[0033] The preparation method of the modified diatomaceous earth described in step S3 is as follows: Add the dried diatomaceous earth to a dilute sulfuric acid solution with a concentration of 3.5 mol / L (the mass ratio of diatomaceous earth to dilute sulfuric acid solution is 1:5), perform ultrasonic treatment under stirring (ultrasonic treatment at 530 kHz for 35 min), filter by suction, dry, and grind to obtain modified diatomaceous earth.
[0034] The preparation method of the mesoporous silica described in step S3 is as follows: Dissolve 7 g of tetramethylammonium hydroxide in 35 g of pentanol, add 9 g of ammonia water and 18 g of ether, stir evenly, dropwise add 28 g of tetramethyl orthosilicate, stir and react for 4.4 h, filter by suction, dry, and calcine at 530 °C for 3.8 h to obtain mesoporous silica.
[0035] The preparation method of the mesoporous carbon described in step S3 is as follows: The dried wheat bran is calcined at 780 °C for 1.0 h in a nitrogen atmosphere, cooled, and then mixed evenly with potassium hydroxide (the mass ratio of wheat bran to potassium hydroxide is 1:2.5). Then it is continuously calcined at 830 °C for 4.3 h in a nitrogen atmosphere, cooled, ground, washed with a hydrochloric acid aqueous solution with a concentration of 0.7 mol / L until neutral, and dried to obtain mesoporous carbon.
[0036] Comparative Example 1 The preparation method of the sulfuric acid production catalyst described in this comparative example is similar to that of Example 3. The difference between this comparative example and Example 3 is that in step S2 of this comparative example, an equal amount of CsNO3 is used instead of Sm(NO3)3·6H2O.
[0037] Comparative Example 2 The preparation method of the sulfuric acid production catalyst described in this comparative example is similar to that of Example 3. The difference between this comparative example and Example 3 is that in step S2 of this comparative example, an equal amount of La(NO3)3 is used instead of Sm(NO3)3·6H2O.
[0038] Comparative Example 3 The preparation method of the sulfuric acid production catalyst described in this comparative example is similar to that of Example 3. The difference between this comparative example and Example 3 is that in step S3 of this comparative example, an equal amount of modified diatomite is used instead of the mesoporous material.
[0039] Comparative Example 4 The preparation method of the sulfuric acid production catalyst described in this comparative example is similar to that of Example 3. The difference between this comparative example and Example 3 is that all of the mesoporous materials in step S3 of this comparative example are mesoporous silica.
[0040] Comparative Example 5 The preparation method of the sulfuric acid production catalyst described in this comparative example is similar to that of Example 3. The difference between this comparative example and Example 3 is that the mesoporous material in step S3 of this comparative example is composed of mesoporous silica and mesoporous carbon in a mass ratio of 2:9.
[0041] Comparative Example 6 The preparation method of the sulfuric acid production catalyst described in this comparative example is similar to that of Example 3. The difference between this comparative example and Example 3 is that an equal amount of deionized water is used instead of the dilute sulfuric acid solution in the preparation process of the modified diatomite in this comparative example.
[0042] Comparative Example 7 The preparation method of the sulfuric acid production catalyst described in this comparative example is similar to that of Example 3. The difference between this comparative example and Example 3 is that potassium hydroxide is not added in the preparation process of the mesoporous carbon in this comparative example.
[0043] Test Example Pore structure test: The pore structure parameters of the catalysts prepared in Examples 1 - 3 and Comparative Examples 3 - 7 were analyzed using an AutoPore IV 9500 mercury porosimeter and an ASAP 2020 physical adsorption analyzer from Micromeritics, USA. The test results are shown in Table 1, and the pore size distribution and adsorption - desorption curves of the catalyst prepared in Example 3 are shown in Figure 4 and Figure 5 .
[0044] Activity test: Referring to the method specified in the Chinese chemical industry standard "HG / T 2089 - 2014 Experimental Method for the Activity of Sulfur Dioxide Oxidation to Sulfuric Acid Catalysts", the catalysts prepared in Examples 1 - 3 and Comparative Examples 1 - 7 were subjected to activity tests on a self - made activity evaluation device (see Figure 1 ). The catalyst was loaded into a quartz tube, heated from room temperature to 200 °C at a rate of 200 °C / h, air was introduced, and then heated to 350 °C. The feed gas containing 3% SO2 was switched, and the space velocity was 7200 h -1 , and then heated to 600 °C and kept at this temperature for 2 h. After activation, it was cooled to the test temperature at a rate of 100 °C / h, and the SO2 concentrations at the inlet and outlet were measured by the iodometric method. Each temperature point was measured in 3 replicates, and the average value was recorded. After loading the catalyst solid into the reactor and ensuring no air leakage, the switch was turned on for the experiment. First, the temperature was increased at a rate of 3 °C per minute. After 60 minutes, dry air was introduced, and the space velocity was controlled at about 3600 h -1 ; after another 45 minutes, high - purity sulfur dioxide was introduced, and the volume fraction of sulfur dioxide was controlled at about 10%. Then, the temperature was continuously increased at a rate of 3 °C per minute to 600 °C and heat - resistant for 5 h. After reaching the heat - resistant time, it was cooled to the active temperatures of 485 °C, 440 °C, 410 °C, and 350 °C at a rate of 200 °C / h. It was stabilized for 1 h in each temperature section, and the SO2 concentrations at the inlet and outlet were measured by the iodometric method in each temperature section. Finally, the conversion rate (E) of SO2 was calculated respectively. The calculation formula is as follows, where: Vin is the volume fraction of SO2 at the inlet, and Vout is the volume fraction of SO2 at the outlet. The test results are shown in Table 2.
[0045]
[0046] Scanning electron microscopy test (SEM): The catalyst prepared in Example 3 was subjected to a scanning electron microscopy test, and the test results are shown in Figure 2 .
[0047] X - ray diffraction test (XRD): The catalyst prepared in Example 3 was subjected to X - ray diffraction analysis test, and the test results are shown in Figure 3 .
[0048] Table 1 Pore structure parameters of the catalyst
[0049] As can be seen from Table 1, the specific surface area of the catalyst for sulfuric acid production provided by the present invention is 11.34 - 15.67 m 2 / g, the pore volume is 2.63 - 3.29 cm 3 / g, and the average pore diameter is 35.96 - 43.21 nm, indicating that the catalyst for sulfuric acid production provided by the present invention has a rich pore structure. Among them, the catalyst prepared in Example 3 has the optimal pore structure parameters and is the best example of the present invention.
[0050] Compared with Example 3, in Comparative Example 3, an equal amount of modified diatomite was used to replace the mesoporous material in step S3, but the pore structure parameters of the prepared catalyst decreased slightly, which was due to the smaller pore structure of the modified diatomite than that of the mesoporous material; in Comparative Example 4, all of the mesoporous materials in step S3 were mesoporous silica, and in Comparative Example 5, the mass ratio of mesoporous silica and mesoporous carbon was changed, but the pore structure parameters of the prepared catalyst decreased to varying degrees, indicating that the components and ratios of the mesoporous materials in the present invention have been optimized; in Comparative Example 6, an equal amount of deionized water was used to replace the dilute sulfuric acid solution in the preparation process of the modified diatomite, and in Comparative Example 7, potassium hydroxide was not added in the preparation process of the mesoporous carbon, but the pore structure parameters of the prepared catalyst decreased significantly, indicating that dilute sulfuric acid solution and potassium hydroxide are the key raw materials for pore expansion in the preparation processes of the modified diatomite and the mesoporous carbon.
[0051] Table 2 Activity test results
[0052] As can be seen from Table 2, for the catalyst for sulfuric acid production provided by the present invention, the conversion rate of SO2 is 93.5% - 98.6% at 485 °C, 93.0% - 98.5% at 440 °C, 91.9% - 98.0% at 410 °C, and 89.3% - 96.8% at 350 °C, which fully demonstrates that the catalyst for sulfuric acid production provided by the present invention has good catalytic activity within a wide temperature range.
[0053] Compared with Example 3, in Comparative Example 1, an equal amount of CsNO3 was used to replace Sm(NO3)3·6H2O in step S2, and in Comparative Example 2, an equal amount of La(NO3)3 was used to replace Sm(NO3)3·6H2O in step S2, but the conversion rate of SO2 of the prepared catalyst decreased significantly, indicating that not all doping with rare earth elements can achieve the technical effect of samarium element; the conversion rate of SO2 of the catalysts prepared in Comparative Examples 3 - 7 decreased, which was due to the change in the pore structure of the catalyst.
[0054] From Figure 2It can be seen that there are obviously regularly arranged pores in the catalyst prepared in Example 3, which are the structural characteristics of diatomite. At the same time, there are also disordered pore structures, which are the structural characteristics of mesoporous silica and mesoporous carbon. There are a small number of finer oxide particles on the surfaces of mesoporous silica and mesoporous carbon. This indicates that the active components in the catalyst provided in this application are not only distributed inside the pores but also around the pores, which can increase the contact frequency between the active components and sulfur dioxide during desulfurization and greatly improve the catalytic activity. In addition, no obvious rod-shaped or granular alkali metal salt crystals are seen in the mesoporous material, indicating that the active components have a high dispersion degree in the catalyst and the catalytic activity is high.
[0055] It can be seen from Figure 3 that the characteristic peaks of K3Na(SO4)2 appear at 2θ of 18.04°, 21.7°, 33.52°, and 45.04°, the characteristic peaks of K3V(SO4)3 appear at 2θ of 27.24° and 35.24°, the diffraction peak of SmVO2SO4 appears at 2θ of 25.76°, the characteristic diffraction peak of amorphous silica appears at 2θ of 23°, and the diffraction peak of V2O5 appears at 2θ of 26.68°.
[0056] It can be seen from Figure 4 that the main pore diameters of the catalyst prepared in Example 3 are distributed in the range of 35 - 65 nm, and the pore size distribution is relatively narrow. The pore volume is calculated to be 3.29 cm 3 / g, and the average pore diameter is 43.21 nm. It can be seen from Figure 5 that the catalyst prepared in Example 3 has a typical type IV isotherm and H1-type hysteresis loop, which indicates that the catalyst sample of this application has typical mesoporous structural characteristics, that is, the loading of the active components does not damage or block the pore channels of the catalyst carrier. Therefore, the catalyst provided in this application not only has a high adsorption capacity for the active components, but also during the desulfurization process, SO2 can smoothly pass through the pore structure to react with the active components, thereby improving the desulfurization efficiency.
[0057] The above embodiments are only illustrative of the present invention and do not limit the present invention. Those skilled in the art shall not modify the above embodiments without departing from the spirit and scope of the present invention. All equivalent modifications or changes completed by those with ordinary knowledge in the technical field without departing from the technical idea of the present invention still fall within the protection scope of the present invention.
Claims
1. A catalyst for sulfuric acid production, characterized in that, It is prepared by the following steps: S1: Dissolve potassium hydroxide in deionized water, stir evenly, heat, add vanadium pentoxide and sodium sulfate, and stir evenly to obtain Solution I; S2: Add concentrated sulfuric acid to Solution I obtained in step S1 under stirring, adjust the pH value of the solution to 2 - 4, and add Sm(NO3)3·6H2O to obtain Solution II; S3: Add modified diatomite and mesoporous material to Solution II prepared in step S2, stir evenly, then perform ultrasonic treatment, form, dry, and calcine to obtain a catalyst for sulfuric acid production; the mesoporous material is composed of mesoporous silica and mesoporous carbon in a mass ratio of 9 - 12:4 - 7.
2. The catalyst for sulfuric acid production according to claim 1, wherein The preparation method of the modified diatomite in step S3 is as follows: Add dry diatomite to a dilute sulfuric acid solution, perform ultrasonic treatment under stirring, filter by suction, dry, and grind to obtain modified diatomite.
3. The catalyst for sulfuric acid production according to claim 2, characterized in that, In the preparation method of the modified diatomite, the mass ratio of the diatomite to the dilute sulfuric acid solution is 1:4 - 6, and the concentration of the dilute sulfuric acid solution is 3 - 4 mol / L; the frequency of the ultrasonic treatment is 500 - 550 kHz, and the ultrasonic treatment time is 30 - 40 min.
4. The catalyst for sulfuric acid production according to claim 1, wherein The preparation method of the mesoporous silica in step S3 is as follows: Dissolve tetramethylammonium hydroxide in pentanol, add ammonia water and ether, stir evenly, dropwise add tetraethyl orthosilicate, stir and react, filter by suction, dry, and calcine to obtain mesoporous silica.
5. The catalyst for sulfuric acid production according to claim 4, wherein, The weight parts of each component in the preparation method of the mesoporous silica are: 5 - 8 parts of tetramethylammonium hydroxide, 30 - 40 parts of pentanol, 8 - 10 parts of ammonia water, 15 - 20 parts of ether, and 25 - 30 parts of tetraethyl orthosilicate.
6. The catalyst for sulfuric acid production according to claim 4, wherein In the preparation method of the mesoporous silica, the stirring reaction time is 4.2 - 4.5 h, the calcination temperature is 500 - 550 °C, and the calcination time is 3.5 - 4 h.
7. The catalyst for sulfuric acid production according to claim 1, characterized in that, The preparation method of the mesoporous carbon in step S3 is as follows: Calcinate the dried wheat bran in a nitrogen atmosphere, cool, mix evenly with potassium hydroxide, continue to calcine in a nitrogen atmosphere, cool, grind, wash with an aqueous hydrochloric acid solution until neutral, and dry to obtain mesoporous carbon.
8. The catalyst for sulfuric acid production according to claim 7, characterized in that, In the preparation method of the mesoporous carbon, the calcination temperature is 750 - 800 °C, and the calcination time is 0.8 - 1.2 h; the temperature of the continued calcination is 800 - 850 °C, and the time of the continued calcination is 4.2 - 4.5 h; the mass ratio of the wheat bran to the potassium hydroxide is 1:2 - 3; the concentration of the aqueous hydrochloric acid solution is 0.5 - 0.8 mol / L.
9. The catalyst for sulfuric acid production according to claim 1, characterized in that, In step S1, the heating temperature is 70 - 75 °C; in step S3, the ultrasonic frequency is 200 - 250 kHz, the ultrasonic time is 10 - 12 h, the drying temperature is 90 - 100 °C, the drying time is 20 - 24 h, the calcination temperature is 550 - 600 °C, the heating rate during calcination is 5 - 10 °C / min, and the calcination time is 5.5 - 6 h.
10. The catalyst for sulfuric acid production according to claim 1, characterized in that, The weight parts of each component are as follows: 15 - 20 parts of potassium hydroxide, 35 - 40 parts of deionized water, 5 - 10 parts of vanadium pentoxide, 2 - 3 parts of sodium sulfate, 1 - 2 parts of Sm(NO3)3·6H2O, 25 - 30 parts of modified diatomite, and 10 - 15 parts of mesoporous material.
Citation Information
Patent Citations
Vanadium catalyst for sulphuric acid production from powdery vanadium pentoxide, and preparation method thereof
CN102974339A
Modifying method of vanadium catalyst for preparing sulfuric acid through sulfur dioxide
CN110052262A
Vanadium-based catalyst and preparation method therefor
CN111065458A
Production process of electronic-grade sulfuric acid
CN116812877A
Improvements in and relating to the oxidation of sulphur dioxide to sulphur trioxideand catalysts therefor
GB808150A
Cited By
Binder for iron powder production
CN120796699A
Preparation method of rubidium salt modified sulfur dioxide oxidation catalyst
CN122124823A
Method for preparing sulfuric acid from pyrite concentrate powder
CN122355242A